Activism and scientific research: 20 years of community action by the Vancouver area network of drug users - Ehsan Jozaghi; Alissa M. Greer; Hugh Lampkin; Jane A. Buxton (BMC, 2018)
Abstract Background Over the past several decades, there have been numerous peer-reviewed articles written about people who use drugs (PWUDs) from the Downtown Eastside neighborhood of Vancouver, Canada. While individual researchers have engaged and acknowledged this population as participants and community partners in their work, there has been comparatively little attention given to the role of PWUDs and drug user organizations in directing, influencing, and shaping research agendas. Methods In this community-driven research, we examine 20 years of peer-reviewed studies, university theses, books, and reports that have been directed, influenced, and shaped by members of the activist organization the Vancouver Area Network of Drug Users (VANDU). In this paper, we have summarized VANDU's work based on different themes from each article. Results After applying the inclusion criteria to over 400 articles, 59 items containing peer-reviewed studies, books, and reports were included and three themes of topics researched or discussed were identified. Theme 1: 'health needs' of marginalized groups was found in 39% of articles, Theme 2: 'evaluation of projects' related to harm reduction in 19%, and Theme 3: 'activism' related work in 42%. Ninety-four percent of co-authors were from British Columbia and 44% of research was qualitative. Works that have been co-authored by VANDU's members or acknowledged their participations created 628 citations. Moreover, their work has been accessed more than 149,600 times. Conclusions Peer-based, democratic harm reduction organizations are important partners in facilitating groundbreaking health and social research, and through research can advocate for the improved health and wellbeing of PWUDs and other marginalized groups in their community. This article also recommends that PWUDs should be more respectfully engaged and given appropriate credit for their contributions.